Reasons for drop-out of peritoneal dialysis in pediatric patients: A single-center experience (Annals of Medical Research, 2021)
Aim: Peritoneal dialysis is the first line treatment for patients with end-stage renal disease in childhood, due to a number of advantages offered. However, patients drop-out for various reasons during the course of the treatment. Identifying and preventing the emergence of those causes is very important for maintaining treatment with peritoneal dialysis. Material and Methods: Patients who were followed up between January 2005 and March 2019 in the peritoneal dialysis outpatient clinic of the Department of Pediatric Nephrology were examined retrospectively. The patients’ demographic data, as well as their reasons for drop-out of treatment were taken from patient files.Results: The results revealed that 89 patients (51.7% female, 48.3% male, mean age 83.17±56.78 months) underwent PD treatment over a period of 14 years and that 12 of them switched to another medical facility during their follow-up and that the peritoneal dialysis treatment of 34 (44.2%) of the remaining 77 patients was discontinued. The average duration of PD treatment was 38.21±27.93 months. In terms of the etiology of end-stage renal disease, urological anomalies (28.1%) and glomerular diseases (25.8%) were the most common. 18 patients (52.9%) dropped out of peritoneal dialysis due to hemodialysis, 11 (32.3%) due to transplantation, 4 (11.7%) due to death, and one (2.9%) due to a break from the treatment. Of the patients who switched to hemodialysis, 11 (61.2%) did so due to recurrent/resistant peritonitis, 4 (22.3%) due to failure of ultrafiltration, 2 (11%) due to mechanical problems (one case of hydrothorax, one case of leakage) while one (5.5%) patient voluntarily switched to hemodialysis.Conclusion: Although peritoneal dialysis offers many advantages in childhood, the transition to HD due to recurrent peritonitis remains the most common cause of peritoneal dialysis treatment discontinuation.
Keywords: Chronic peritoneal dialysis; drop-out; pediatric patients